HUMANISM IN EDUCATION - Tambunan, Frietz R. (UNIKA Santo Thomas, 2003)
The formation of the person is not a new issue in the history of the development of human resource or in the history of education. Scholars have put it as their main concern since the archaic reflection on education in particular when they spoke about an exact method in educating young people. This problem remains real, up until the modern time especially with the existence of new experiment in education and the application of ‘high tech’ in educations sectors. In the minds of all our modern tendencies, people are likely to be treated only as ‘things’, as an objects of new experimentation, and not as persons. This article, will highlight the importance of the person and personal approaches in the process of education as the true way of the formation of a person. This has a great importance due to the fact that education in our modern society has been strongly influenced by utilitarianism and we need to dig up the humanism concept in confronting such strong tendency.